MicroRNA and cellular targets profiling reveal miR-217 and miR-576-3p as proviral factors during Oropouche infection - Geddes, Victor Emmanuel Viana; de Oliveira, Anibal Silva; Tanuri, Amilcar; Arruda, Eurico; Ribeiro-Alves, Marcelo; Aguiar, Renato Santana (PLOS Neglected Tropical Diseases, 2018)
Oropouche Virus is the etiological agent of an arbovirus febrile disease that affects thousands of people and is widespread throughout Central and South American countries. Although isolated in 1950’s, still there is scarce information regarding the virus biology and its prevalence is likely underestimated. In order to identify and elucidate interactions with host cells factors and increase the understanding about the Oropouche Virus biology, we performed microRNA (miRNA) and target genes screening in human hepatocarcinoma cell line HuH-7. Cellular miRNAs are short non-coding RNAs that regulates gene expression post-transcriptionally and play key roles in several steps of viral infections. The large scale RT-qPCR based screening found 13 differentially expressed miRNAs in Oropouche infected cells. Further validation confirmed that miR-217 and miR-576-3p were 5.5 fold up-regulated at early stages of virus infection (6 hours post-infection). Using bioinformatics and pathway enrichment analysis, we predicted the cellular targets genes for miR-217 and miR-576-3p. Differential expression analysis of RNA from 95 selected targets revealed genes involved in innate immunity modulation, viral release and neurological disorder outcomes. Further analysis revealed the gene of decapping protein 2 (DCP2), a previous known restriction factor for bunyaviruses transcription, as a miR-217 candidate target that is progressively down-regulated during Oropouche infection. Our analysis also showed that activators genes involved in innate immune response through IFN-β pathway, as STING (Stimulator of Interferon Genes) and TRAF3 (TNF-Receptor Associated Factor 3), were down-regulated as the infection progress. Inhibition of miR-217 or miR-576-3p restricts OROV replication, decreasing viral RNA (up to 8.3 fold) and virus titer (3 fold). Finally, we showed that virus escape IFN-β mediated immune response increasing the levels of cellular miR-576-3p resulting in a decreasing of its partners STING and TRAF3. We concluded stating that the present study, the first for a Peribunyaviridae member, gives insights in its prospective pathways that could help to understand virus biology, interactions with host cells and pathogenesis, suggesting that the virus escapes the antiviral cellular pathways increasing the expression of cognates miRNAs.